2022
DOI: 10.3390/s22166225
|View full text |Cite
|
Sign up to set email alerts
|

Smart Technologies for Water Resource Management: An Overview

Abstract: The latest progress in information and communication technology (ICT) and the Internet of Things (IoT) have opened up new opportunities for real-time monitoring and controlling of cities’ structures, infrastructures, and services. In this context, smart water management technology provides the data and tools to help users more effectively manage water usage. Data collected with smart water devices are being integrated with building management systems to show how much water is used by occupants as well as to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 112 publications
0
5
0
Order By: Relevance
“…It is intended to provide some details regarding the possible applications, the sensors exploited, and the characteristics of the wireless communication channel. More exhaustive reviews on such topics can be found in the literature [2,4,6,[28][29][30][31].…”
Section: Review Of Swg Based On Standard Radio Communicationmentioning
confidence: 99%
See 2 more Smart Citations
“…It is intended to provide some details regarding the possible applications, the sensors exploited, and the characteristics of the wireless communication channel. More exhaustive reviews on such topics can be found in the literature [2,4,6,[28][29][30][31].…”
Section: Review Of Swg Based On Standard Radio Communicationmentioning
confidence: 99%
“…As was presented in the previous Sect., SWGs deal with the management of water distribution networks [1]. As far as the communication network of such SWGs is concerned, it results from previous reviews [2][3][4][5] that the vast majority of the cases employ radio wave communication for information transfer between sensor nodes of the network. However, the review [1], among the various wireless techniques, also considered acoustic wave-based communication as a possible way to transfer information, since it is effectively a wireless communication technique.…”
Section: Acoustic Based Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the growing importance and progress of IoT technologies and the high demand for smart cities that require IoT applications in managing infrastructure, systematic reviews (SR) about using IoT applications in infrastructure management are few and far between [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46]. While existing reviews have concentrated on specific dimensions of IoT applications in water management, such as IoT's role in stormwater management [45], leakage monitoring [36], and the implementation of intelligent utilities in urban contexts [41], [42], [43], [44], the demand for a more all-encompassing review is discernible.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, high quality of life in a green economy will only be possible by effectively orchestrating a great wealth of fused information, which will be created from an immense number of smart sensor networks. Smart sensors are already in demand in diverse areas of utilization, including modern energy systems, energy-smart buildings, water resource management in urban and farming applications, healthcare operations, as well as in environmental air-quality monitoring and processed food improvement [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%